1987
DOI: 10.1136/jnnp.50.9.1211
|View full text |Cite
|
Sign up to set email alerts
|

A portable system for measuring cutaneous thresholds for warming and cooling.

Abstract: SUMMARY Measurement of cutaneous thermal thresholds is a valuable technique for detecting small fibre neuropathy. A robust and portable microcomputer controlled system, which separately measures thresholds for warming and cooling, is described. Thresholds at three sites have been measured; the cheek, the dorsum of the hand and the sole of the foot. Regional variability and a correlation with age have been found, indicating the sensitivity of this system. Psychophysical estimates of cutaneous thresholds for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(38 citation statements)
references
References 9 publications
0
36
2
Order By: Relevance
“…Winer et al (1992) found the upper limits of the temperature threshold of the foot to be lower than in our study (e.g. warm sensation up to 1.08C for normal controls and 8.08C for those with neuropathy), which may re¯ect differences in methodology, since the thermode was placed on the plantar rather than the dorsal surfaces of the feet (Fowler et al, 1987), thermal properties of the skin show marked variation between sites (Stevens et al, 1974). Winer et al (1992) also preceded their tests by establishing an approximate value for the threshold before ®ne tuning the measurements, a step which we have omitted.…”
Section: Discussioncontrasting
confidence: 80%
“…Winer et al (1992) found the upper limits of the temperature threshold of the foot to be lower than in our study (e.g. warm sensation up to 1.08C for normal controls and 8.08C for those with neuropathy), which may re¯ect differences in methodology, since the thermode was placed on the plantar rather than the dorsal surfaces of the feet (Fowler et al, 1987), thermal properties of the skin show marked variation between sites (Stevens et al, 1974). Winer et al (1992) also preceded their tests by establishing an approximate value for the threshold before ®ne tuning the measurements, a step which we have omitted.…”
Section: Discussioncontrasting
confidence: 80%
“…1,5,6,11,13,17,18,22,32,33,44 Our results emphasize the necessity of including an adequate representation of older subjects, especially when investigating the discriminative properties of the test. The most striking effect of age was seen in vibration thresholds, which become increasingly variable for subjects over the age of 65 years.…”
Section: Discussionmentioning
confidence: 82%
“…42 A somewhat weaker but similar effect has been seen for thermal thresholds. 5,6,11,17,32,33 Analyses are frequently stratified by gender, but this effect on sensation thresholds may be confounded by height differences. 29 In studies where height was measured, it was associated with an increase in threshold values in the lower limbs.…”
mentioning
confidence: 99%
“…That is, thermal sensitivity will decline in a similar manner between males and females with the ageing process. In contrast, Fowler et al [5346] reported greater increases in the warm threshold detection (i.e. sensitivity declined) in comparison to cold threshold detection in aged individuals; suggesting that the unmyelinated fibres were age affected.…”
mentioning
confidence: 80%